QUESTION SUBJECT AND PRINCIPLES OF AIR LAW: economic patriotism as the principle RIGHTS - Костицький, В. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article raises questions object and air law principles.